Private Desires, Political Action : an Invitation to the Politics of Rational Choice. - Laver, Michael John (Sage Publications, 1997)
Private Desires, Political Action is an accessible overview of one of the most important approaches to the study of politics in the modern world - rational choice theory. Michael Laver does not set out to review this entire field, but rather to discuss how we might use rational choice theory to analyze the political competition that affects almost every aspect of our lives. The broad-ranging scope of the book introduces the theory at many levels of analysis, including: the private desires of individuals; the social context of how people fulfil their desires; and the problems of collective acti.